X-ray Photoelectron Spectroscopy Investigation over Supported Palladium Catalyst Prepared using Water-in-oil Microemulsion - Hoi Jin, Wong; Ambar Yarmo, Mohd; Radiman, Shahidan; Ramli, Anita; Atan, Hafidz; Chow Khim, Tan (Malaysian Journal of Science, 2002)
Supported palladium catalysis have been prepared using water-inÃ¢â‚¬â€oil microemulsion consisting of Pd(NOÃ¢â€šÆ’)Ã¢â€šâ€š aq, Brij 30 (surfactant) and n-hexane (oil). The binding energies of palladium from those catalysts were measured using x-ray photoelectron spectroscopy (XPS) and were compared with that of the catalysts prepared by conventional impregnation method. It was observed that the majority of the palladium is present at a binding energy shifted between 0.8 to 1.0eV higher than the impregnation catalysts observed for PdO. Such shift appeared to be associated with a metal-support interaction where the palladium was very small in size and highly dispersed. These findings were supported with a much higher activity in methane combustion under lean conditions. However, not only the size and dispersity of palladium that determined their catalytic performance, it was found that the active phase or state of the catalysts that existed during the reaction has great influence on the catalyst activity. The result showed PdO was the most active state for methane combustion but it did not rule out the possibilities of a mixed phase. PdÃ¢ÂÂ°/PdO_x.